Hidden pressurized fluids prior to the 2014 phreatic eruption at Mt Ontake - Corentin Caudron; Yosuke Aoki; Thomas Lecocq; Raphael De Plaen; Jean Soubestre; Aurelien Mordret; Leonard Seydoux; Toshiko Terakawa (Nature Communications, 2022)
Phreatic volcanic eruptions can be unexpected and devastating. Here the authors, using seismic-based methodologies, find that pressurized fluids accumulated 5 months before the deadly phreatic eruption at Mt Ontake; a period previously considered as completely quiescent.